An algebra problem by Martin Nikolov

Algebra Level 1

If a , b a, b are non-zero real numbers such that a b = a b ab = a - b , evaluate

a b + b a a b . \frac { a}{b} + \frac{ b}{a} - ab .


Note: This problem is not original.


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

7 solutions

Chew-Seong Cheong
Nov 26, 2014

Squaring both sides of a b = a b a 2 b 2 = a 2 2 a b + b 2 ab = a - b \quad \Rightarrow a^2b^2 = a^2 - 2ab + b^2

Dividing both sides with a b a b = a b 2 + b a ab \quad \Rightarrow ab = \dfrac {a}{b} - 2 + \dfrac {b} {a}

Rearranging, we have a b + b a a b = 2 \dfrac {a}{b} + \dfrac {b} {a} - ab = \boxed {2}

nice solution sir

Mardokay Mosazghi - 6 years, 6 months ago
Rick B
Dec 3, 2014

a b + b a a b = ( a b a ) + ( b a + b ) = a a b b + b + a b a \dfrac{a}{b}+\dfrac{b}{a}-ab = \left(\dfrac{a}{b}-a\right)+\left(\dfrac{b}{a}+b\right) = \dfrac{a-ab}{b}+\dfrac{b+ab}{a}

= a ( a b ) b + b + ( a b ) a = b b + a a = 1 + 1 = 2 = \dfrac{a-(a-b)}{b}+\dfrac{b+(a-b)}{a} = \dfrac{b}{b}+\dfrac{a}{a} = 1+1 = \boxed{2}

Solve for a We equate equation with any number. For example b = 3 Now we have two values a = -1.5 and b = 3. Solve for in the last formula

Pd. I'm 15 years old

Vishal S
Dec 22, 2014

a/b+b/a - ab=a^2+b^2/ab - ab

We can write a^2+b^2 /ab - ab as (a-b)^2+2ab/ab - ab

But given a-b=ab

By substituting a-b=ab in (a-b)^2+2ab/ab - ab

We get a^2.b^2 + 2ab/ab - ab

=a^2.b^2 + 2ab - a^2.b^2 / ab

=2ab/ab

=2

Wijil Pambudi
Dec 9, 2014

ab=a-b ==> a=-2 ; b=2 now put in a/b +b/a-ab ==> -1-1+4 = 2

We get by squaring both sides in the given information:

a b = a b a 2 b 2 = ( a b ) 2 a 2 b 2 = a 2 + b 2 2 a b \displaystyle ab = a-b \Rightarrow a^{2}b^{2} = (a-b)^2 \Rightarrow a^{2}b^{2} = a^{2} + b^{2} - 2ab

Dividing both sides by ab , we get:

a b = a b + b a 2 a b + b a a b = 2 \displaystyle ab = \frac{a}{b} + \frac{b}{a} - 2 \Rightarrow \frac{a}{b} + \frac{b}{a} - ab = \boxed{2}

And hence the answer!

a/b+b/a=(a^2+b^2)/ab Now ,(ab)^2=(a-b)^2 So, (a^2+b^2-a^2-b^2+2ab)/ab So, 2ab/ab=2

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...